Improving Playfair Algorithm To Support User Verification And All The Languages In The World Including Kurdish Language (International Journal of Engineering and Computer Science, 2015)
communicating over any untrusted medium or network requires privacy and authentication; cryptography plays an important role in this area. Original Playfair cipher is one of the early cryptographic algorithms that uses a 5x5 matrix. It supports English language merely and can be cracked easily. It has being improved in different aspects. This paper, firstly, improves the algorithm to support the Kurdish language script. This is achieved by using a 256X256 matrix that meanwhile increases the security of the algorithm dramatically. Secondly, the proposed algorithm is coupled with a hash function (sha512) to achieve user verification. For this a software is designed and implemented based on software development concepts.